The handbook of fashion studies - Black, Sandy; De la Haye, Amy; Entwistle, Joanne ca. 20. Jh; Rocamora, Agnès; Root, Regina A.; Thomas, Helen 1947- (Bloomsbury, 2018)
The handbook is an invaluable resource for students and scholars, providing a comprehensive and innovative overview of the field of fashion studies. The outstanding scholarly articles point the way forward for research. Thematically structured and accessibly written, the work illustrates the potential of interdisciplinary fashion research
First published as hardback edition in 2013
Keywords: Gesellschaft; Globalisierung; Theorie; Mode; Fashion / Handbooks, manuals, etc; Clothing and dress / Handbooks, manuals, etc; Clothing trade / Handbooks, manuals, etc; Beauty and Fashion; Clothing and dress; Clothing trade; Fashion; Handbooks and manuals; Aufsatzsammlung